Medicine safety seminar for Malaysian community pharmacists - Hassali, Mohamed Azmi; Palaian, Subish; Shafie, Asrul Akmal; Elkalmi, Ramadan Mohamed Mahmod; Shrestha, Rishi (Wiley Online Library, 2009)
Although medicines are beneficial in improving health status, they are associated with inescapable risks. Adverse drug reactions are one of the major limiting factors associated with medicine use. 1 A strategy used to minimise adverse drug reactions is educating health professionals on risk minimisation and early detection of adverse drug reaction